Prevalence of non-communicable diseases in Brazilian children: follow-up at school age of two Brazilian birth cohorts of the 1990's - Loureiro Sônia R; Pereira Thaís S; Rodriguez Juliana D; Silva Nathalia A; Figueiredo Maria L; Gutierrez Manoel R; Vianna Elcio O; Simões Vanda M; Batista Rosângela F; Cardoso Viviane C; Barbieri Marco A; Silva Antônio A; et al. (BMC, 2011)
Abstract Background Few cohort studies have been conducted in low and middle-income countries to investigate non-communicable diseases among school-aged children. This article aims to describe the methodology of two birth cohorts, started in 1994 in Ribeirão Preto (RP), a more developed city, and in 1997/98 in São Luís (SL), a less developed town. Methods Prevalences of some non-communicable diseases during the first follow-up of these cohorts were estimated and compared. Data on singleton live births were obtained at birth (2858 in RP and 2443 in SL). The follow-up at school age was conducted in RP in 2004/05, when the children were 9-11 years old and in SL in 2005/06, when the children were 7-9 years old. Follow-up rates were 68.7% in RP (790 included) and 72.7% in SL (673 participants). The groups of low (<2500 g) and high (≥ 4250 g) birthweight were oversampled and estimates were corrected by weighting. Results In the more developed city there was a higher percentage of non-nutritive sucking habits (69.1% vs 47.9%), lifetime bottle use (89.6% vs 68.3%), higher prevalence of primary headache in the last 15 days (27.9% vs 13.0%), higher positive skin tests for allergens (44.3% vs 25.3%) and higher prevalence of overweight (18.2% vs 3.6%), obesity (9.5% vs 1.8%) and hypertension (10.9% vs 4.6%). In the less developed city there was a larger percentage of children with below average cognitive function (28.9% vs 12.2%), mental health problems (47.4% vs 38.4%), depression (21.6% vs 6.0%) and underweight (5.8% vs 3.6%). There was no difference in the prevalence of bruxism, recurrent abdominal pain, asthma and bronchial hyperresponsiveness between cities. Conclusions Some non-communicable diseases were highly prevalent, especially in the more developed city. Some high rates suggest that the burden of non-communicable diseases will be high in the future, especially mental health problems.